Respuesta :

Answer:

x=1

Step-by-step explanation:

[tex] \frac{5(x + 6) - 15(2 - x)}{3x - 1} = 10 \\ [/tex]

[tex] = > 5(x + 6) - 15(2 - x) = 10(3x - 1)[/tex]

[tex]5x + 30 - 30 + 15x = 30x - 10[/tex]

[tex] = > 20x = 30x - 10 \\ = > 20x - 30x = - 10 \\ = > - 10x = - 10 \\ = > x = 1[/tex]

hope it helps:)

Start by expanding the numerator.

5x+30-30+15x / 3x-1 = 10

Simplify.

20x / 3x-1 = 10

Multiply both sides by the denominator.

20x = 30x-10

Divide both sides by 20.

x = 3/2-1/2

Subtract the fractions.

x = 1